Renal function and linear growth of children with nephrocalcinosis: a retrospective single-center study - Doğan, Cağla Serpil; Uslu-Gökçeoğlu, Arife; Comak, Elif; Alimoğlu, Emel; Koyun, Mustafa; Akman, Sema (The Turkish Journal of Pediatrics, 2013)
The aim of this study was to analyze the etiology of nephrocalcinosis (NC) and whether it has any effect on growth and renal function in children. Forty-three children who were diagnosed with bilateral NC were studied retrospectively. Two neonates treated with furosemide and five premature infants were excluded from the study. The most common condition leading to NC was hereditary tubulopathies (50%). Data of 27 children who had a follow-up period of at least two years were examined in more detail. Of the 27 patients, the median age at first examination was 12 (range: 2-132) months and median follow-up time was 57 (range: 24-209) months. Thirteen of 27 (48.1%) patients had height standard deviation scores (hSDS)